2001
DOI: 10.1161/hy1101.092967
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Determinants of Plasma Nitrogen Oxides and Risk of Ischemic Heart Disease

Abstract: Abstract-Endothelial dysfunction, caused in part by reduced NO bioavailability, is a feature of hypercholesterolemia, hypertension, smoking, and atherosclerosis. We examined whether cholesterol, blood pressure, smoking status, and polymorphisms in the endothelial NO synthase gene (NOS 3) influence NO production (as assessed by the plasma levels of nitrogen oxides, NO x ) in middle-aged men. We also determined whether plasma NO x or NOS 3 genotype predicted the risk of ischemic heart disease (IHD). We studied 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
61
1
8

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 53 publications
11
61
1
8
Order By: Relevance
“…The allelic frequencies in our control group were in agreement with other studies, [43][44][45][46] and the linkage disequilibrium between the T-786C and E298D polymorphisms also confirmed previous reports. 46,47 The single locus findings were confirmed by the results of our 2-locus genotype analysis, with a lower risk for POTS in individuals homozygous for -786C and 298D, based on OR and 95% CI. Although haplotype analysis also indicated a significant difference between the POTS and control groups, we chose to focus on the results of genotype analyses, which are more biologically meaningful.…”
Section: Discussionsupporting
confidence: 93%
“…The allelic frequencies in our control group were in agreement with other studies, [43][44][45][46] and the linkage disequilibrium between the T-786C and E298D polymorphisms also confirmed previous reports. 46,47 The single locus findings were confirmed by the results of our 2-locus genotype analysis, with a lower risk for POTS in individuals homozygous for -786C and 298D, based on OR and 95% CI. Although haplotype analysis also indicated a significant difference between the POTS and control groups, we chose to focus on the results of genotype analyses, which are more biologically meaningful.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, another association study between genetic polymorphisms of the eNOS gene and hypertension in Japanese has recently shown that the T 786 3 C polymorphism is significantly linked to the Glu 298 3 Asp polymorphism with trans configuration (the T 786 allele is linked to the Asp 298 and the C 786 allele to the Glu 298 ) (24 ). In this study we found that the Asp 298 allele is weakly but significantly linked to the C 786 allele of the T 786 3 C polymorphism in the 5Ј-flanking region of the eNOS gene; this evidence is in agreement with that recently reported in another European population in terms of both extent of disequilibrium and allele frequency (25 ).…”
Section: Discussionsupporting
confidence: 93%
“…Other investigators previously found the eNOS Glu298Asp polymorphism to be related to the presence of atherosclerotic manifestations such as coronary artery disease 29 -31 and carotid atherosclerotic plaques, 32 although negative reports have also been published. 28 Because atherosclerotic renovascular disease is generally viewed as a local manifestation of systemic atherosclerotic disease, at least our data in ARASϩ are in line with these earlier observations. Even the results in ARASϪ patients may be compatible with more severe atherosclerosis in these individuals.…”
Section: Van Onna Et Al Candidate Genes In Renal Artery Disease 451supporting
confidence: 89%